Elucidating the genomic and transcriptomic landscape of L858R vs ex19del EGFR-mutated NSCLC - Pang, Mengyuan; Yeo, Jia Chi; Alvarez, Jacob; Sim, Ngak Leng; Ng, Win Pin; Lai, Gillianne; Tan, Aaron C.; Jain, Amit; Tan, Wan Ling; Kanesvaran, Ravindran; Ng, Quan Sing; Lim, Darren Wan-Teck; et al. (Journal of clinical oncology, 2023)
8530Background: Epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) is heterogeneous and L858R derive less benefit from osimertinib than ex19del in both the metastatic and adjuvant setting, which remains poorly understood. We sought to examine the genomic and transcriptomic features of L858R vs ex19del. Methods: Consecutive patients with AJCC7 Stage IA-IIIA EGFR-mutated NSCLC diagnosed 1/1/2010 - 31/12/2019 who underwent surgery at National Cancer Centre Singapore were included. Patients who received neoadjuvant therapy were excluded. Fresh frozen tumour and normal samples were subject to whole exome sequencing (WES) at 400X and 100X coverage respectively, with approximately 50 million paired-end reads for RNA-seq per sample. Wilcoxon and Fisher's exact test were used for association analysis. Results: A total of 203 patients were included. Median age at diagnosis was 66, 66.0% (134/203) were females and 84.2% (171/203) never-smokers. Stage IA comprised 44.3% (90/203), IB 28.6% (58/203), II 15.8% (32/203) and IIIA 11.3% (23/203). Median tumour mutational burden (TMB) was 1.3 mutations/megabase (range 0.3 - 44.3). Ex19del represented 46.3% (94/203) and L858R 41.9% (85/203). Whole genome doubling (WGD) was found in 70.0% (142/203) and was more common in TP53-mutated compared to TP53-wildtype (81.1% vs. 63.6%, p=0.01). TP53 mutations were more common in stage II/IIIA tumours compared with stage IB and IA (50.9% vs 32.8% vs 30.0%, p=0.035). Comparing ex19del and L858R, there was no difference in stage distribution (p=0.337), proportion of TMB≥10 (1.1% vs 5.9%, p=0.103), number of cancer co-driver mutations (p=0.174), TP53 mutations (39.4% vs 32.9%, p=0.437) and WGD (69.1% vs 76.5%, p=0.316). L858R had a higher incidence of smoking mutational signature (median 0.35 vs 0.28, p=0.018) compared to ex19del despite similar smoking history (15.3% vs 12.8%, p=0.67), whereas APOBEC mutational signature was higher in ex19del (median 0.06 vs 0.04, p=0.015). L858R tumors were associated with a higher incidence of co-mutations in RBM10 (21.2% vs 6.38%, p=0.004), RNF213 (10.6% vs 1.06%, p=0.007) and amplification of NTHL1 (15.3% vs 2.13%, p=0.001) and AXIN1 (17.6% vs 3.19%, p=0.002) compared to ex19del. Transcriptomic subtype differed significantly by EGFR mutation with a higher representation of TRU subtype among L858R than ex19del (51.0% vs 35.3%, p=0.010), while GEP score was similar (median 0.189 vs 0.325, p=0.122). Conclusions: L858R have distinct co-mutations and copy number alterations compared to ex19del, in addition to a higher representation of smoking mutational signature and TRU subtype. TP53 co-mutations are more frequently observed in higher stage tumours and are associated with WGD. Our findings highlight the molecular heterogeneity of resected EGFR-mutated NSCLC, which could contribute to the differential outcomes to adjuvant osimertinib between ex19del and L858R.